2006
DOI: 10.1038/sj.onc.1209988
|View full text |Cite
|
Sign up to set email alerts
|

PHC3, a component of the hPRC-H complex, associates with 2A7E during G0 and is lost in osteosarcoma tumors

Abstract: Polyhomeotic-like 3 (PHC3) is a ubiquitously expressed member of the polycomb gene family and part of the human polycomb complex hPRC-H. We found that in normal cells PHC3 associated with both hPRC-H complex components and with the transcription factor E2F6. In differentiating and confluent cells, PHC3 and E2F6 showed nuclear colocalization in a punctate pattern that resembled the binding of polycomb bodies to heterochromatin. This punctate pattern was not seen in proliferating cells suggesting that PHC3 may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Polyhomeoticlike protein 3 is part of the polycomb PRC1 complex involved in long-term gene silencing (33), and the protein is believed to be a tumor suppressor protein (34). Another tumor suppressor protein, particularly associated with breast and ovarian cancer, is EMSY, a transcriptional repressor of the BRCA2 gene (35).…”
Section: Functions Of the Identified O-glcnac-modified Proteinsmentioning
confidence: 99%
“…Polyhomeoticlike protein 3 is part of the polycomb PRC1 complex involved in long-term gene silencing (33), and the protein is believed to be a tumor suppressor protein (34). Another tumor suppressor protein, particularly associated with breast and ovarian cancer, is EMSY, a transcriptional repressor of the BRCA2 gene (35).…”
Section: Functions Of the Identified O-glcnac-modified Proteinsmentioning
confidence: 99%
“…Also, E2F6 has been shown to interact with PcG proteins, which are known to regulate HOX genes. For example, E2F6 has been shown to interact with Polyhomeotic-like (PHC3) (Isono et al 2005;Deshpande et al 2007) and with BMI1 (Trimarchi et al 2001), two members of the hPRC-H family of PcG proteins. One study copurified E2F6 with EZH2 (Attwooll et al 2005) and we have previously shown that Ezh2 binds to the promoters of hundreds of homeobox genes ).…”
Section: Figurementioning
confidence: 99%
“…To the best of our knowledge, PHC3 genomic amplification and mRNA upregulation have never been described before. However, PHC3 has been found to be downregulated in human sarcomas, where it acts as a tumour suppressor (Deshpande et al , 2007). …”
Section: Discussionmentioning
confidence: 99%
“…PhC proteins bridge distant chromatin templates, thereby recruiting PRC1 to selected loci (Lavigne et al , 2004). Currently, three PhC isoforms are known, with different tissue distribution and partially overlapping functions (Deshpande et al , 2007). PRC1 has been implicated in tumorigenesis and progression of several cancer types.…”
Section: Discussionmentioning
confidence: 99%